An unusual case of achalasia cardia mimic: why cant I cut it trough? - Nik Muhamad Affendi, Nik Arsyad; Ho, Shiaw Hooi; Lau, Peng Choong; Mahadeva, Sanjiv (2023)
Per-oral endoscopic myotomy (POEM) has become the main modality for the treatment of achalasia which is a motility disorder characterised by failure of lower oesophageal sphincter relaxation and loss of oesophageal peristalsis. Herein we report a rare case of achalasia mimic that was diagnosed after a failed POEM procedure. A 28-year-old lady was referred to our centre with a worsening dysphagia for 6-month. She had a history of dysphagia since she was 3 year-old. Oesophagogastroduodenoscopy showed smooth narrowing at distal oesophagus with no mucosa lesion seen. CT scan showed long segment circumferential thickening of the lower oesophagus without extrinsic compression. Oesophageal manometry showed type-3 achalasia changes (see figure 1). During POEM procedure, GOJ was determined at 39cm distance from incisor. However, a tight narrowing was encountered at 37cm preventing further tunneling beyond that point. Myotomy-first approach was attempted at this narrowed region but was unsuccessful in loosening the tight narrowing. Nonetheless, myotomy was carried out from 30cm till the point of narrowing. Due to risk of mucosal injury, further procedure was abandoned. The patient was subsequently referred to an UGI surgeon for salvage laparoscopic Heller’s myotomy. However, the surgery was unsuccessful and was complicated with a small iatrogenic perforation at distal oesophagus. Eventually, distal oesophagectomy was carried out and the patient made an uneventful recovery. A circumferential hard whitish tissue within the thickened oesophagus was seen at distal oesophagus during the surgery (see figure 2). Histology from the surgical specimen revealed the presence of ectopic cartilage plate and sero-mucinous glands. This case highlighted the potential of misdiagnosis despite the current standard diagnostic modalities for achalasia cardia. However, ectopic oesophageal cartilage resulting in luminal narrowing in the distal oesophagus is a rare condition which mimics achalasia. EUS assessment may perhaps be helpful in detecting such cartilage tissue within the narrowed oesophagus.